Combination of Misoprostol with Transcervical Foley’s Catheter Compared to Misoprostol Alone for Cervical Ripening at Term and Labour Induction in Tertiary Care Hospital: A Randomized Trial - Minal Kalambe (Akare)1 , Mugdha L. Jungari2 , Priya Pratapan Nair2 , Dipti Shrivastava3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background:Induction of labour is a very common in obstetrics, for that both mechanical and pharmacologicalmethod used for induction. Mechanical Foley’s with misoprostol is an effective method to cut out course oflabour in safe timely manner, for safe neonatal and maternal outcome.Aims and Objective: The aim of this study was to compare combination of transcervical Misoprostol withFoley’s catheter balloon to misoprostol alone for induction of labour and cervical ripening in uncomplicatedpregnancy, with regards to safety and effectiveness.Result: A prospective, randomized controlled study was conducted on 220 term singleton women admittedin our hospital for induction of labour were randomly allocated to Group 1 (combination of Foley’s andmisoprostol) and Group 2 means (misoprostol) each 110. Combination of Foley’s and vaginal misoprostolwas much more effective in nulliparous female than multiparous women. Induction delivery interval wasshorter in combination group;14.4±5.70 hours than misoprostol group; 17.1±5.62 hours; p value is 0.007.Conclusion: This study showed that the use of misoprostol with a trans cervical Foley’s is an effective methodto shorten the course of labour compared with misoprostol alone. This study suggest that combination maybe useful to achieve safe and timely delivery in unripe cervix.